Shugan Hewei Decoction Alleviates Cecum Mucosal Injury and Improves Depressive- and Anxiety-Like Behaviors in Chronic Stress Model Rats by Regulating Cecal Microbiota and Inhibiting NLRP3 Inflammasome - Yue, Yingying; Chen, Yu; Liu, Hao; Xu, Lesi; Zhou, Xian; Ming, Hao; Chen, Xin; Chen, Miaoqi; Lin, Yunya; Liu, Lin; Zhao, Yingqian; Liu, Songlin (Frontiers in Pharmacology, 2021)
Chronic stress is a significant cause of depression, anxiety, and intestinal mucosal injury. Gut microbiota disturbances are also associated with these disorders. Shugan Hewei Decoction (SHD), which is a traditional Chinese medicine formula developed by our team, has shown superior therapeutic effects in the treatment of depression, anxiety, and functional gastrointestinal diseases caused by chronic stress. In this study, we investigated the modulatory effect of SHD on the cecal microbiota and cecum mucosal NOD-like receptor protein 3 (NLRP3) inflammasome in a chronic unpredictable stress (CUS)/social isolation rat model. After the SHD intervention, the CUS model rats showed improvements in their depressive- and anxiety-like behaviors, as well as sustained body weight growth and improved fecal characteristics. SHD improved the cecal microbiota diversity and changed the abundance of six microbial genera. A Spearman’s correlation analysis showed a strong correlation between the NLRP3 inflammasome and CUS-perturbed cecal biomarker microbiota. SHD regulated the excessive expression of NLRP3, ASC, caspase-1, interleukin-1β (IL-1β), and IL-18 in the serum and cecum mucosa induced by CUS, as well as the activation of the Toll-like receptor 4/nuclear factor-κB signaling cascades. Our results reveal the pharmacological mechanisms of SHD and provide a validated therapeutic method for the treatment of depression, anxiety, and cecum mucosal injury.